2005
DOI: 10.1148/radiol.2373041919
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic-Clinical Correlation in Severe Acute Respiratory Syndrome: Study of 1373 Patients in Hong Kong

Abstract: The initial extent of radiographic opacification may be useful for prognostic prediction. Radiographic progression correlates well with that of important clinical and laboratory parameters and may be used as an objective prognostic indicator early in SARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
6
24
2
Order By: Relevance
“…The maximal radiographic score correlated best with the percentage of lymphocytes in a leukocyte count, followed by the number of hospitalized days and the absolute lymphocyte count.. The above findings were somewhat different from findings in other series (27, 29, 32, 38). …”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The maximal radiographic score correlated best with the percentage of lymphocytes in a leukocyte count, followed by the number of hospitalized days and the absolute lymphocyte count.. The above findings were somewhat different from findings in other series (27, 29, 32, 38). …”
Section: Discussioncontrasting
confidence: 58%
“…Three of the 28 patients expired with a mortality rate of 10.7%, which is comparable to that seen overall in Taiwan (12.3%), Hong Kong (11.7%), and worldwide (9.6%) (4, 27). It has been reported that for patients with SARS, old age and comorbities are more likely to be associated with a high mortality (17-20).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In this series, only 42% of patients demonstrate positive findings and this is likely due to the range of clinical presentation of the study population. Several studies have a similar initial CXR positive findings of 42-50% for this disease [12, 13]. …”
Section: Discussionmentioning
confidence: 66%
“…Other changes recorded on CT were focal or multifocal consolidation, interstitial changes and pulmonary embolism [4, 13, 14]. CT was valuable in detecting positive findings in the presence of normal CXRs and showed more extensive pattern of involvement when compared to CXR [14].…”
Section: Discussionmentioning
confidence: 99%